2017
DOI: 10.1073/pnas.1712465114
|View full text |Cite|
|
Sign up to set email alerts
|

Taurine ameliorates particulate matter-induced emphysema by switching on mitochondrial NADH dehydrogenase genes

Abstract: SignificanceExposure to high levels of particulate matter (PM) poses a major threat to human health. Cigarette smoke is the most common irritant that causes chronic obstructive pulmonary disease (COPD); however, at least one-fourth of patients with COPD are nonsmokers, and their disease is largely attributed to air pollution. The occurrence of pollution episodes in China has raised an emergent question of how PM leads to the pathogenesis of COPD. In this paper, we show that deregulation of mitochondrial NADH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Mitochondria are energy factories in eukaryotic cells, which can provide energy for various physiological activities of the body [7]. With the occurrence of mitochondrial oxidative phosphorylation, a large number of ROS will be produced, and excessive ROS will lead to mitochondrial damage, causing apoptosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are energy factories in eukaryotic cells, which can provide energy for various physiological activities of the body [7]. With the occurrence of mitochondrial oxidative phosphorylation, a large number of ROS will be produced, and excessive ROS will lead to mitochondrial damage, causing apoptosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…12) Also, previous studies have demonstrated that the correla-tion between PM2.5 and invasion of lung cancer cells. 13) Although the relation between extended exposure to PM and risk of lung cancer is established, the defense mechanism of PM-induced pulmonary fibrosis is still poorly understood. Antioxidant-rich diets or chemicals might be potentially useful in ameliorating the effects of PM by counteracting the associated oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the flavour‐related substances, taurine content was higher in the S. paramamosain , especially in the hepatopancreas of crab (Wang et al, ). Taurine has many functions such as anti‐tumour, enhancing immunity, protecting heart, lowering blood pressure, lowering blood lipid, lowering blood sugar, reducing fatty liver, lowering transaminase and anti‐ageing, and it is an important nutrient and health material in the diet (Huxtable, ; Li et al, ; Zhang et al, ) . Organic acid is an important flavour substance, and its composition and content are closely related to metabolism (Tao et al, ; Yeh, de Moura, Van Den Broek, & de Mello, ).…”
Section: Introductionmentioning
confidence: 99%